TMOD-14. A PATIENT-DERIVED CANCER CELL LINE ATLAS OF PRIMARY AND METASTATIC CENTRAL NERVOUS SYSTEM TUMORS. (5th November 2018) - De Smet, Frederik; Tseng, Yuen-Yi; Ramkissoon, Shakti; Ramkissoon, Lori; Pelton, Kristine; Luna, Ruben Ferrer; Panovska, Dena; Schoolcraft, Kate; Watkinson, Fiona; Bilton, Shawna; Hung, Victoria; Chow, Kin-Hoe; et al.
Abstract: BACKGROUND: Tumors involving the central nervous system (CNS) include over 200 primary and metastatic subtypes with major clinical impact. Research on CNS neoplasms has been hampered by the lack of appropriate models for many subtypes. We established a robust workflow and systematic culturing approach to create cancer cell line models from all adult and pediatric CNS cancer patients and here report the results of these ongoing efforts. METHODS: Tumor samples from consented patients with CNS cancers were systematically collected from 2008–18. Tumors were grown in different media and substrates and growth verified by >5 passages. Genomic verification was performed using NGS analysis (focused SNV and CNA) and expression profiling assays. RESULTS: We attempted to generate cell line models from >1500 consented brain tumor patients at the Brigham and Women's and Boston Children's Hospital (IRB-10–417) under the DFCI Living Tissue Bank Program as well as within the Broad Institute Cancer Cell Line Factory (CCLF) Project and the Leuven Living Tissue Bank (IRB-S59804, Belgium). 120 different tumor types, including high and low-grade brain tumors of both adult and pediatric origin, were evaluated for in vitro growth in >2000 culturing attempts. The success rate of growing high-grade tumors (i.e. glioma and of other origin) was robustly high (~50%), while the growth verification rate for low-grade tumors remained low (<1%). Overall, growth beyond passage 5 was achieved in ~30% of cases, and of the growth verified models, also ~30% were genomically verified to represent cancer, with the majority maintaining genomic and/or transcriptional features. In addition to primary CNS tumors, we were now also able to grow metastatic cultures, resulting in >150 novel model systems covering >20 primary and metastatic diagnoses. CONCLUSION: Patient-derived cell lines may be created at scale from primary and metastatic CNS tumors to support pre-clinical cancer research but technological improvements will be required to culture even more tumor types.